ANALISIS DAN EVALUASI EFEKTIVITAS SOP PERUSAHAN DALAM MENCEGAHAN FRAUD DI PERUSAHAAN STUDI KASUS PADA PT ABC - Aswarul Haq; Regina Jansen Arsjah (JURNAL LENTERA BISNIS, 2025)
Standard Operating Procedures (SOPs) are essential work guidelines designed to ensure that all activities within a company are carried out effectively, consistently, and systematically. However, the continued occurrence of fraud despite the implementation of SOPs indicates potential weaknesses in their effectiveness. This study aims to analyze and evaluate the effectiveness of SOPs in preventing fraud at PT ABC. A qualitative case study approach was employed, utilizing field observation, in-depth interviews, and internal documentation analysis. The results reveal that several SOPs at PT ABC are outdated and lack critical provisions related to sales confirmation, receivables monitoring, warehouse control, and operational fuel usage. These gaps create opportunities for fraud, particularly involving sales, warehouse, and logistics staff. This study offers practical contributions through recommendations for improving SOPs to strengthen the company’s internal control system. The findings underscore the importance of regular SOP evaluation to ensure their relevance to operational dynamics and their effectiveness in fraud prevention.